DESIGNING STAGES OF LEARNING FOR CHILDREN WITH CEREBRAL PALSY IN MEMORIZING THE QURAN - Hanik Fitriyatun; Subar Junanto (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
This research was conducted based on the need to identify the learning stages of children with cerebral palsy in relation to their potential to memorize the Qur’an. The purpose of this study was to find out the stages of learning carried out by parents and teachers in teaching children with cerebral palsy to memorize the Qur’an. The method used in this study was a qualitative method with a case study design. Data collection techniques used interviews, observation and documentation. To test the validity of the data, triangulation techniques was used and interactive models was implemented to analyze the data. The results of the study show that the learning stages in teaching children with Cerebral Palsy to memorize the Qur’an are by analyzing the learning types of children with Cerebral Palsy, being used to listening to the Qur’an verses, monitoring their progress with routine murajaah and supporting them with educational facilities based on their development needs. Keywords: Learning Stages, Children with Cerebral Palsy, Memorizing the Qur'an